INTEGRASI NILAI-NILAI ISLAM PADA SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU SEKOLAH - Sholihah Imro’atus (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
This article aims to determine the integration of Islamic values in educational supervision in improving the quality of schools in several Islamic institutions in Jember district. This method uses a qualitative approach with a case study method and the data in this study were collected through observation, in-depth interviews, and documentation studies and data analysis techniques in this study using the Miles and Huberman interactive analysis model which includes data reduction, data presentation, and drawing conclusions. From the results of the study here is the first, namely to improve teacher professionalism: in supervision based on Islamic values, it contributes to improving teacher professionalism by instilling Islamic moral and ethical values so that teachers have a high sense of discipline and are responsible in carrying out their duties. Second is strengthening the character of students: in the Integration of Islamic supervision has an impact on the formation of the character of students who are more moral and oriented towards Islamic values, the third is Increasing Learning Effectiveness where Teachers who receive Islamic supervision guidance are more creative in developing interactive teaching methods, the fourth is the Challenge in Implementing Islamic Value-Based Supervision, One of the main challenges in the implementation of Islamic supervision is the low understanding of educators regarding the concept of supervision based on Islamic values and the fifth is the Strategy for Optimizing Islamic Value-Based Supervision To overcome the existing challenges, several strategies are needed to optimize supervision based on Islamic values. One of them is by holding routine training for educators to better understand the concept of Islamic supervision